The Theoretical Study of an Interconnected Suspension System for a Formula Student Car - Pridie, Andrei-Cristian; Antonya, Csaba (MDPI AG, 2021)
When it comes to racing applications, the primary engineering goal is to increase the performance envelope of the vehicle for a given set of tires. To achieve this goal, it is necessary to maximize the normal loads on the wheels while at the same time minimizing the tire load variation. The purpose of this paper is to present a mathematical model for a Formula Student car in order to study if performance gains are achieved by replacing the traditional passive suspension with a hydraulically interconnected suspension system. To have a complete picture of the advantages and disadvantages of each system, two vibrating models with 7 degrees of freedom were created in order to simulate the motion response of a Formula Student car to realistic excitations. Two particular interpretations of the results were chosen as important performance indicators. The first one is given by the pitch stability of the chassis relative to the road, which can be linked with a decrease in downforce load variation. The second one is the ability of the wheel to follow the road profile as closely as possible, which can be directly correlated with the amount of mechanical grip of the vehicle. The simulation results indicate that the hydraulically interconnected suspension system offers better results for both proposed cases but at the expense of the roll stability of the vehicle.
Keywords: hydraulic suspension; vibrating model; formula student; interconnected suspension